2018
DOI: 10.2337/dc18-1178
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Insulin Resistance in Youth on the Spectrum From Normal Weight to Obese and From Normal Glucose Tolerance to Impaired Glucose Tolerance to Type 2 Diabetes

Abstract: Adipose tissue insulin resistance is one of the pathophysiological components of type 2 diabetes. Herein we investigated: 1) adipose insulin resistance index (Adipose-IR) (calculated as fasting insulin 3 free fatty acids [FFAs]) in youth across the spectrum of adiposity from normal weight to obese and the spectrum from normal glucose tolerance (NGT) to impaired glucose tolerance (IGT) to type 2 diabetes, 2) the relationship of Adipose-IR with physical and metabolic characteristics, and 3) the predictive power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 39 publications
(55 reference statements)
3
69
1
6
Order By: Relevance
“…Increasing adiponectin expression reduces metabolic abnormalities associated with obesity and T2D. Our data are in agreement with a previous report (48) that ADP concentrations are reduced in prediabetes and T2D. Our data are also consistent with the findings that ADP knockout mice have decreased mitochondrial content in skeletal muscle associated with insulin resistance and mitochondrial dysfunctional skeletal muscle (49): and that adiponectin may affect mitochondrial biogenesis (30).…”
Section: Discussionsupporting
confidence: 93%
“…Increasing adiponectin expression reduces metabolic abnormalities associated with obesity and T2D. Our data are in agreement with a previous report (48) that ADP concentrations are reduced in prediabetes and T2D. Our data are also consistent with the findings that ADP knockout mice have decreased mitochondrial content in skeletal muscle associated with insulin resistance and mitochondrial dysfunctional skeletal muscle (49): and that adiponectin may affect mitochondrial biogenesis (30).…”
Section: Discussionsupporting
confidence: 93%
“…The chronic inflammation in the adipose tissue or liver, mainly during obesity, has been linked to insulin sensitivity [153]. Furthermore, adipose tissue insulin resistance is one of the pathophysiological components of type 2 diabetes [154]. On the contrary, correlation of Cdc42 and IR in some tissues (such as skeleton muscles and neuron cells) remains unclear and shows significant variety in our review [86,87].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, most studies which employed AT-IR investigated people with obesity and/or type 2 diabetes and were conducted in Western countries. [10][11][12][13][14][15][16] We, therefore, investigated determinants, correlates and usefulness of AT-IR in Japanese women without diabetes and obesity, populations in which confounding factors are so scarce. 17 Because we have shown that endurance training lowered AT-IR in young women, 18 we excluded female collegiate athletes in the present study.…”
mentioning
confidence: 99%